Gender-Related Reporting Within Foot and Ankle Subspecialty Orthopaedic Literature is Lacking. Issue 4 (16th October 2019) - Gianakos, Arianna L.; George, Nicole; Merklein, Meghan; Chambers, Lori; Daniel, Joseph; DiGiovanni, Christopher; Kennedy, John G
Category: Ankle, Arthroscopy, Hindfoot, Midfoot/Forefoot, Trauma Introduction/Purpose: Differences in the prevalence of foot and ankle injuries between men and women have been established within the orthopedic literature, but reporting of these differences in treatment outcomes is lacking. The purpose of this study was to determine the trends in reporting of gender-specific outcomes in major orthopaedic foot and ankle related journals over the last 8 years. Methods: The five highest impact orthopaedic foot and ankle and sports specialty journals were selected for review. These included: Foot and Ankle International (FAI), Foot and Ankle Surgery (FAS), American Journal of Sports Medicine (AJSM), Arthroscopy, and Knee Surgery, Sports Traumatology, Arthroscopy (KSSTA). All published issues in 2011 and 2016 were evaluated for the presence of gender-specific analyses by two independent reviewers. Studies were included if they met the following criteria: clinical randomized control studies, prospective studies, and retrospective studies. Case series, review articles, cadaveric studies, biomechanical studies, and animal studies were excluded. Journal article, percentage of female patients, body part evaluated, type of gender-specific analysis, and results of the analysis were recorded and analyzed. Results: A total of 529 studies evaluating a total of 103, 099 patients were included in this review (Table 1). In all included studies, an average of 44.7% (46, 116 patients) of the population were female. Only 13.6% (72/529) of studies included gender as variable in a multifactorial statistical model. 229 studies were included from 2011 and 300 studies were included from 2016 with only 10.4% (24/229) and 16.0% (48/300) of studies reporting gender specific statistical analysis, respectively (Table 2). There were no journals that demonstrated significant improvements in gender-reported rates from 2011 to 2016 (p=0.07). Twenty-four percent of the studies that performed gender-based statistical analysis demonstrated significant differences between male and female outcomes with the most common difference reported following management of ankle fractures (Table 3). Conclusion: The reporting of gender-specific differences in foot and ankle literature is lacking. Only 13.6% of studies analyzed for gender-specific differences. Within these studies, there has been significant differences in outcomes reported. Understanding these differences is important in order to more effectively manage and treat the male and female populations.